Technical viability study of steel slag as non -conventional material in concrete / Kamran Shavarebi - Shavarebi, Kamran (Institute of Graduate Studies, UiTM, 2017)
Although recycling of waste material has started since the last few decades, recycling as a means of sustainable use of Non-Conventional material did not actually start until fairly recently. Recycling of industrial waste and byproduct material which is an environmentally sensitive problem faced by waste manager throughout the world is no exception. Specifically steelmaking operations are concerned by this problem because of the generation of a huge quantity of by - products such as Electric Arc Furnace Slag (EAFS). Basically, there are two reasons to the rationale underlying the usage of slag as a source of aggregate; the need to conserve natural resources and the need to manage waste amicably. However, to make the feasible acceptance of slag as aggregate in concrete, its strength, deformation and durability must also be assured. This research attempts to provide that assurance by conducting a comprehensive investigation on the strength, deformation and durability performance. This study is divided into four (4) main phases: (i) chemical and physical properties of slag and its suitability as aggregate for concrete production (ii) design of mix proportions of SSA using replacement level of 0%, 10%, 50% and 100%. Six (6) series of concrete specimen were cast. The series refer to the difference of w/c ratios between the ranges 0.47 – 0.7. The specimens were tested from 3 days until 365 days (iii) the engineering properties considered include compressive, tensile and flexural strength, modulus of elasticity and drying shrinkage…